An Investigation of Exchange Rate Volatility using Econometric Model: Evidence from Cambodia - Ky, Sereyvath (Journal of Ecohumanism, 2025)
The examination of foreign exchange dynamics was performed utilizing the Autoregressive Integrated Moving Average (ARIMA) model, which integrates both Autoregressive (AR) and Moving Average (MA) components. The analysis focused on the monthly exchange rate between the Khmer Riel and the US dollar, spanning from December 2018 to September 2024, to assess the variations in exchange rates. According to the results of the Augmented Dickey-Fuller (ADF) test, the foreign exchange data series was determined to be integrated of order zero, or I(0). The model identified as the most appropriate, based on the Akaike Information Criterion (AIC), was the ARIMA(3,0,3) model, which indicated the optimal lag lengths for this analysis. The reaction of the foreign exchange market to the disturbance shock revealed a cyclical behavior and demonstrated a downward trajectory over the 30-period forecast horizon. Importantly, the impulse response function (IRF) stayed within the 95% confidence interval, signifying that the response to the shock was statistically significant and remained within a tolerable level of uncertainty. This observation implies that the predictions generated by the model can be regarded as trustworthy.